Polymeric Hollow Fibers: State of the Art Review of Their Preparation, Characterization and Applications in Different Research Areas - Khulbe, K.C.; Feng, C.; Matsuura, T.; Khayet, M. (Journal of Applied Membrane Science & Technology, 2017)
In this article an attempt is made to review critically the papers published recently on polymeric hollow fibers and hollow fiber membranes. Hollow fiber membranes emerged in early nineteen sixties at almost the same time as the announcement of the cellulose acetate reverse osmosis membrane for seawater desalination by Loeb and Sourirajan. Since then, the hollow fiber technology has progressed along with the industrial membrane separation processes. Today, hollow fiber membranes are being used in every sector of the manufacturing industry, including gas and vapor separation, seawater desalination and waste water treatment. The fabrication of a hollow fiber membrane with a desirable pore–size distribution and performance is not an easy task. There are many factors controlling fiber morphology during the phase inversion process and, at present, we are not able to say that we fully understand the phenomena involved in the fabrication of hollow fibers. Nevertheless, there has been a large amount of knowledge accumulated during the past fifteen years, which has been supported by an equally large amount of efforts by many researchers. This paper attempts to summarize those works. The authors could however look into only those reports which have appeared in scientific journals and few patents, and they are fully aware that there must be much more information that has not surfaced to the journal publication. It is also the authors’ intention to show the future direction including the research topics that have been studied only little or not at all.